Generation of Indene Derivatives by Tandem Reactions - Qiu, Guanyinsheng; Wu, Jie (Synlett, 2014)
As a privileged motif, the indene core can be found in many natural products and pharmaceuticals. Our continued interest in the construction of natural product like compounds prompted us to develop efficient and mild protocols for the generation of indene derivatives. This account describes two typical procedures that involve tandem reactions: a base-mediated cyclization of 1-alkenyl-2-arylalkynes and a palladium-catalyzed annulation of 1-alkynyl-2-halobenzenes. Diversity and complexity can be easily incorporated during these reaction processes.1 Introduction2 Synthesis of Indene Derivatives by Base-Promoted Cyclization of (2-Alkenylphenyl)alkynes3 Formation of Indenes by Palladium-Catalyzed Reactions of gem-Dibromoolefins4 Palladium-Catalyzed Reactions of 1-Alkynyl-2-bromobenzenes5 Outlook and Conclusion
Keywords: indenes; catalysis; palladium; tandem reaction; cyclization